The Numerical Modelling of the Flow in Hydrocyclones - Andrzej F. Nowakowski; Michael J. Doby (KONA Powder and Particle Journal, 2014)
Over the last decade, the progress in numerical modelling of hydrocyclones has advanced at a rapid pace. A summary of the recent advancements is undertaken in the paper to summarize the major directions and developments in hydrocyclone modelling. The important aspects that contribute to the accurate simulation of general internal swirling flows and other characteristic features occurring in hydrocyclones modelling are covered. The relevant issues are: the formulation of the governing equations (classical versus stress divergence form), the imposition of boundary conditions especially regarding the open part of the outlet boundary conditions and the problem of proper representation of the computational domain. The complex flow pattern that occurs in hydrocyclones invalidates several assumptions in the standard turbulence models. Challenges still remain in predicting accurately the effects of turbulence anisotropy. A performance review of selected equations closures is presented with insight on their potential and limitations. The flow predictions obtained using the Reynolds Stress Model (RSM) and Large Eddy Simulation (LES) turbulence models are examined. The predictions of the free surface flow and air core dimensions have yet to be fully resolved. The same concerns the problem of simulating large number of particles. The recent important developments related to the solid/gas and sold/liquid interaction problems are presented together with intriguing challenges one need to overcome in order to numerically handle multi-component flows. The Lagrangian and multi-continuum Eulerian techniques are considered. The attempt to systemize various approaches for multi-component flows according to their accurateness and relevance to the various flow regimes in hydrocyclones is undertaken. The issue of experimental validation is crucial to provide confidence in hydrocyclone flow-field models and the current state of experimental data is examined. Finally, suggestions for the future direction of hydrocyclone modelling are highlighted.